Negotiating dignity in public geography: The ethics of public engagement in pandemic times. Issue 1 (20th July 2022) - Plyushteva, Anna
Abstract: In this paper, I reflect on some of the ethical dimensions of public engagement with geographic research. The paper draws on my recent experience of a project entitled 'Not working from home', which sought to make visible the everyday experiences of essential workers during the COVID‐19 pandemic. The project was intended as a space for essential workers to document their daily lives using text, images and video, enabling them to engage with each other, while also informing the wider public about the everyday challenges of not working from home during the pandemic. The paper discusses some of the ethical implications and challenges of conducting this project, drawing on a critical engagement with dignity as an ethical framework for public engagement. I discuss the implications of calling workers 'essential', the role of collective and professional identities explored by the participants, and the impact of offering rewards. I also ask some broader questions on the role that the concept of dignity might play in the ethics of public engagement with research in human geography. Short Abstract: Dignity is a widely used concept and one with a deeply problematic history. In different ways, it is already being used in geographic research. This paper uses the example of the Not working from home project to discuss what a relational understanding of the concept of dignity can bring to the ethics of public engagement with research in geography.